Solve for z -cz+6z=to+83

answer: o Step-by-step explanation: Rearrange the equation by subtracting what is to the right of the equal sign from both sides of the equation :

-c*z+6*z-(t*o+83)=0 Step by step solution :

Step 1 :

Pulling out like terms :

1.1 Pull out like factors :

-cz + 6z – to – 83 = -1 • (cz – 6z + to + 83) Equation at the end of step 1 :

Step 2 :

Solving a Single Variable Equation :

2.1 Solve -cz+6z-to-83 = 0 hope you understand brainliest

z = 83/( -c+6-t) Step-by-step explanation: -cz + 6z = tz + 83 Subtract tz from each side -cz + 6z -tz= tz-tz + 83 -cz + 6z – tz = 83 Factor out z z( -c+6-t) = 83 Divide each side by ( -c+6-t) z( -c+6-t)/( -c+6-t) = 83/( -c+6-t) z = 83/( -c+6-t)

- Men and Women of the Civil War Crossword? - February 1, 2023
- What phone company is this: Stpcs Joint Venture, Llc? - January 31, 2023
- 750+ Creative & Unique Gaming Channel Names | Random Gaming Channel Names Generator - January 31, 2023